Influence of biochar on the water permeability of compacted clay subjected to freezing–thawing cycles - Chen, Zhongkui; Kamchoom, Viroon; Leung, Anthony Kwan; Xue, Jiaxiang; Chen, Rui (My University, 2024)
Seasonal variation of soil surface temperature, such as freezing and thawing, can induce increases in the water permeability in clay by mobilizing clay pore structure. This kind of weather-induced change in clay behavior may worsen the water-sealing performance during the construction and after closure operation of engineered structures such as soil barriers for tailings or man-made slopes. There is limited knowledge towards the influence of freezing–thawing cycles on clay microstructure and saturated permeability (Ksat). This study investigated the saturated permeability of clay under freezing–thawing cycles and explored the uses of biochar as eco-friendly amendment to manipulate the permeability of compacted clay. Clay specimens were compacted with different initial water contents (30%, 34%, and 38%). The biochar application rates of 0%, 2%, 4%, 8% (by dry weight) were applied to measure their effects on the permeability of clay specimens. Saturated permeability was measured by the falling head tests. Any variation of biochar amended clay microstructure after freezing–thawing cycles was captured by the scanning electron microscope. The Ksat was reduced by about one order of magnitude when the biochar application rate was larger than 4%. This may be attributed to the increase in the filling of the biochar particles in the clay intra-aggregate pores upon the transport of liquid water during the repeated freezing–thawing processes. The biochar may thus be recommended to minimize the Ksat of geo-environmental structures in cold regions when sufficiently large application rate was used to facilitate the pore-filling process.
Keywords: Biochar; Compacted clay; Freezing–thawing; Saturated permeability